Pembelajaran Pendidikan Agama Hindu Dan Budi Pekerti Dalam Perspektif Tri Kaya Parisudha di Kelas X SMA Negeri 9 Denpasar - I Kadek Agus Budiyasa; Gede Rai Parsua; I Nengah Arimbawa (Jayapangus Press, 2026)
Education plays an important role in shaping students’ character through a learning process that emphasizes not only cognitive aspects but also attitudes, morals, and behavior. In Hindu Religious Education and Character Education, the teaching of Tri Kaya Parisudha serves as an ethical foundation for developing harmony among thoughts, speech, and actions. This study aims to describe and analyze the learning process of Hindu Religious Education and Character Education from the perspective of Tri Kaya Parisudha and its implications for the character formation of Grade X students at SMA Negeri 9 Denpasar. This study employed a descriptive qualitative approach. Data were collected through non-participant observation, semi-structured interviews, literature study, and documentation. The data were analyzed through data classification, data reduction, data presentation, and conclusion drawing. The findings show that the learning process was implemented through lectures, discussions, habituation, and religious practices that integrated the values of manacika, wacika, and kayika. The value of manacika was instilled through the reinforcement of positive, reflective, and religious thinking; the value of wacika was developed through the habituation of polite, honest, and respectful communication; while the value of kayika was realized through disciplined, responsible, cooperative, and socially caring actions. The learning process also encouraged students’ active involvement through direct experiences in religious and social activities within the school environment. The implications of learning were reflected in changes in students’ attitudes and behavior, as they became more polite, orderly, caring, and able to control their thoughts, speech, and actions. Thus, Hindu Religious Education and Character Education based on Tri Kaya Parisudha contributes to holistic student character formation.